Peranan Nilai Nilai Pancasila Dalam Menciptakan Karakter Siswa Di Lingkungan Madrasah Tsanawiyah Aisyiah Binjai - Muhammad Yusuf (Yayasan Rahmat Islamiyah, 2023)
The background of this research turns out to be developing capabilities and shape the character and civilization of a dignified nation as well. To educate the nation's life, it is necessary to instill values .Pancasila which aims to develop the potential of students so that to be a man of faith and piety to God Almighty, noble, healthy, knowledgeable, capable, creative, independent, and a citizen. Democratic and responsible country. The purpose of this research is to find out how the planting of Pancasila values is carried out teachers in cultivating the religious character of madrasa students know what are the obstacles faced by teachers in planting Pancasila values in growing the religious character of students. The results of this study are planting carried out by the school in cultivating the religious character of students on Pancasila values, namely by using the and approach method exemplary, and the obstacles faced by teachers in instilling values. Pancasila in cultivating the religious character of students, namely the first is the absence of awareness in children, second. Environmental Influence, third, Lack of guidance, fourth, Busy People Old.